Surgical repair of rectovaginal fistula by combined transanal and transvaginal endoscopy: a case report - He, Tian; Zhang, Wen; Mao, Nian-fen; Bai, Xuan; Zhao, Lin; Yue, Ke-lin; Yang, Guo-qing; Rao, Chun-mei; Wang, Jing (Frontiers in Gastroenterology, 2024)
The common causes of rectovaginal fistula include obstetric trauma, local infection, and rectal surgery, while rectovaginal fistula following hemorrhoid surgery is extremely rare. Rectovaginal fistulae (RVF) rarely heal without intervention. Surgical treatment is usually performed, but the optimal surgical method remains controversial. The patient was a 37-year-old woman who was transferred to our hospital due to an unsuccessful repair of a rectovaginal fistula after hemorrhoid surgery in a local hospital. The next day after admission, she had prophylactic ileostomy, fecal diversion and combined treatment with cephalosporin antibiotic to create a clean postoperative area. However, there was still fecal outflow from the vagina, with no significant reduction in excretion compared to previous surgery. Digestive endoscopy confirmed a failure of the repair for rectovaginal fistula. Therefore, preventive ileostomy was continued to reduce the accumulation of bacteria in the fistula and control the inflammation. After 8 weeks, the endoscopic fistula inflammation disappeared, and the condition of endoscopic surgery was considered to be mature. Subsequently, a new surgical method combining transanal endoscopy and transvaginal endoscopy was performed. After 12 weeks of surgery, a follow-up endoscopic examination showed that the fistula had been repaired and healed. During the 1-year follow-up, no serious complication was encountered, no recurrence was found, and the repair effect was satisfactory. In conclusion, a new technique combining transanal endoscopy and transvaginal endoscopy can effectively be used for the surgical repair of rectovaginal fistula after a hemorrhoid operation.